Understanding Resilience, Risk, and Protection in the light of School Attendance and Dropout : a Comparative Cross-Case Analysis of Qualitative Data in Vietnam (2011)
This paper asks the following question “Why do some children drop out halfway through school while others, with similar backgrounds and conditions, do not?”. A comparative cross-case study based on qualitative data collected from 12 children aged 16-17, their caregivers, friends, teachers and community people in two villages in Vietnam is used to examine the factors influencing children’s different pathways through high school. Using the resilience framework, both the risk and protective factors at the individual, family, friendship, and school levels pertaining to these high school attendees and drop-outs will be explored. The study suggests that the presence of certain protective factors might have helped some children overcome the adversity of their situation and continue high school, while the presence of certain risk factors might have discouraged other children, having contributed to their inability to develop resilience. Differences among gender and ethnic groups will be discussed and implications for parents and educators will also be drawn.